2002
DOI: 10.1177/10791102009002009
|View full text |Cite
|
Sign up to set email alerts
|

The Schedule for Nonadaptive and Adaptive Personality (Snap)

Abstract: The authors investigated the test-retest reliability and predictive validity of the diagnostic scales from the Schedule for Nonadaptive and Adaptive Personality (SNAP). Participants were identified from a sample of 240 undergraduates who completed the SNAP and the Social Adjustment Scale (SAS-SR) at Time 1. The authors selected 50 people who met criteria for a personality disorder (PD) based on the SNAP and 50 who did not qualify for a diagnosis. Eighty-three of these people completed the SNAP and the SAS-SR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…(Melley, et al, 2002) Our results support the predictive validity of the diagnostic scales on the SNAP (Clark, 1993). SNAP scores can predict cluster A and C diagnoses.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…(Melley, et al, 2002) Our results support the predictive validity of the diagnostic scales on the SNAP (Clark, 1993). SNAP scores can predict cluster A and C diagnoses.…”
supporting
confidence: 78%
“…Clark (1993) found that the SNAP scores correlated on average .54 to DSM-IV diagnoses-a coefficient surprisingly high for a self-report instrument. Melley, Oltmanns and Turkheimer (2002) investigated the test-retest reliability and predictive validity of the SNAP; there were satisfactory levels of temporal stability (.58 to .81), however the authors found mixed support for its predictive validity. The SNAP scores did modestly predict cluster A and C PD onset.…”
Section: Continuedmentioning
confidence: 99%
“…This diagnostic scale is based on 27 items from the SNAP, with higher scores indicating higher levels of borderline symptoms (α=0.86). Adequate reliability and validity have been shown for this diagnostic scale (e.g., Melley et al, 2002; Reynolds and Clark, 2001). …”
Section: Methodsmentioning
confidence: 97%
“…[19,22] Prior studies have reported good internal consistency and test-retest reliabilities of the SNAP scales, and both the temperament and abnormal personality dimensions show appropriate convergent correlations with other personality inventories. [34,35] Additionally, cross-sectional research has shown the SNAP dimensions to be concurrently associated with internalizing diagnoses in patient populations. [24] In the present study, internal consistency estimates were adequate for all SNAP scales (median Cronbach’s alpha: .80; range: .75–.86).…”
Section: Methodsmentioning
confidence: 99%